Remarkable efficiency of a pin-II proteinase inhibitor sans two conserved disulfide bonds is due to enhanced flexibility and hydrogen bond density in the reactive site loop - Joshi, Rakesh S.; Mishra, Manasi; Tamhane, Vaijayanti A.; Ghosh, Anirban; Sonavane, Uddhavesh; Suresh, C. G.; Joshi, Rajendra; Gupta, Vidya S.; Giri, Ashok P. (Journal of Biomolecular Structure & Dynamics, 2014)
Capsicum annuum (L.) expresses diverse potato type II family proteinase inhibitors comprising of inhibitory repeat domain (IRD) as basic functional unit. Most IRDs contain eight conserved cysteines forming four disulfide bonds, which are indispensible for their stability and activity. We investigated the functional significance of evolutionary variations in IRDs and their role in mediating interaction between the inhibitor and cognate proteinase. Among the 18 IRDs encoded by C. annuum, IRD-7, -9, and -12 were selected for further characterization on the basis of variation in their reactive site loop, number of conserved cysteine residues, and higher theoretical G(bind) for interaction with Helicoverpa armigera trypsin. Moreover, inhibition kinetics showed that IRD-9, despite loss of some of the disulfide bonds, was a more potent proteinase inhibitor among the three selected IRDs. Molecular dynamic simulations revealed that serine residues in the place of cysteines at seventh and eighth positions of IRD-9 resulted in an increase in the density of intramolecular hydrogen bonds and reactive site loop flexibility. Results of the serine residues chemical modification also supported this observation and provided a possible explanation for the remarkable inhibitory potential of IRD-9. Furthermore, this natural variant among IRDs showed special attributes like stability to proteolysis and synergistic inhibitory effect on other IRDs. It is likely that IRDs have coevolved selective specialization of their structure and function as a response towards specific insect proteases they encountered. Understanding the molecular mechanism of pest protease-plant proteinaceous inhibitor interaction will help in developing effective pest control strategies.An animated interactive 3D complement (I3DC) is available in Proteopedia at http://proteopedia.org/w/Journal:JBSD:39
Keywords: Capsicum annuum; Helicoverpa armigera; Proteases; Proteinase inhibitor

Structural features of diverse Pin-II proteinase inhibitor genes from capsicum annuum - Mahajan, Neha S.; Dewangan, Veena; Lomate, Purushottam R.; Joshi, Rakesh S.; Mishra, Manasi; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2015)
The proteinase inhibitor (PI) genes from Capsicum annuum were characterized with respect to their UTR, introns and promoter elements. The occurrence of PIs with circularly permuted domain organization was evident. Several potato inhibitor II (Pin-II) type proteinase inhibitor (PI) genes have been analyzed from Capsicum annuum (L.) with respect to their differential expression during plant defense response. However, complete gene characterization of any of these C. annuum PIs (CanPIs) has not been carried out so far. Complete gene architectures of a previously identified CanPI-7 (Beads-on-string, Type A) and a member of newly isolated Bracelet type B, CanPI-69 are reported in this study. The 5' UTR (untranslated region), 3'UTR, and intronic sequences of both the CanPI genes were obtained. The genomic sequence of CanPI-7 exhibited, exon 1 (49 base pair, bp) and exon 2 (740 bp) interrupted by a 294-bp long type I intron. We noted the occurrence of three multi-domain PIs (CanPI-69, 70, 71) with circularly permuted domain organization. CanPI-69 was found to possess exon 1 (49 bp), exon 2 (551 bp) and a 584-bp long type I intron. The upstream sequence analysis of CanPI-7 and CanPI-69 predicted various transcription factor-binding sites including TATA and CAAT boxes, hormone-responsive elements (ABRELATERD1, DOFCOREZM, ERELEE4), and a defense-responsive element (WRKY71OS). Binding of transcription factors such as zinc finger motif MADS-box and MYB to the promoter regions was confirmed using electrophoretic mobility shift assay followed by mass spectrometric identification. The 3' UTR analysis for 25 CanPI genes revealed unique/distinct 3' UTR sequence for each gene. Structures of three domain CanPIs of type A and B were predicted and further analyzed for their attributes. This investigation of CanPI gene architecture will enable the better understanding of the genetic elements present in CanPIs.
Keywords: CanPI; Capsicum; Gene architecture; Promoter; Proteinase inhibitor